"It Was the Best of Times, It Was the Worst of Times": A Qualitative Investigation of Perfectionism and Drinking Narratives in Undergraduate Students. Issue 6 (December 2018) - Nealis, Logan J.; Mackinnon, Sean P.
Perfectionism is a transdiagnostic risk factor for mental health and interpersonal difficulties, but research on perfectionism and alcohol use in emerging adults remains equivocal. Qualitative research methods are underutilized in this area, and inductive analysis of drinking narratives in undergraduate perfectionists may help clarify conflicting results and support novel approaches to quantitative inquiry in this area. We interviewed 20 undergraduates high in perfectionism (6 adaptive perfectionists and 14 maladaptive perfectionists) using a narrative interview, with analyses focusing on a situation involving alcohol use. We coded interviews for emergent themes using thematic analysis. Five themes emerged as follows: (1) drinking as a social experience, (2) suffering consequences, (3) learning from alcohol, (4) alcohol use as escapism, and (5) reluctance and moderation. Our results add to existing literature by highlighting the interpersonal conflict in perfectionistic people's experience in relation to alcohol use during emerging adulthood. Results also suggest perfectionistic people may use alcohol and intoxication as a way to facilitate a "release" from unpleasant situations or emotions. Perfectionists reported both positive and negative experiences, which lends support for using a narrative perspective to help overcome preexisting assumptions about adaptive and maladaptive qualities of perfectionism.